2012
DOI: 10.1007/s12350-012-9517-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of caffeine on adenosine-induced reversible perfusion defects assessed by automated analysis

Abstract: There was no significant relationship between the extent of adenosine-induced coronary flow heterogeneity and the serum concentration of caffeine or its principal metabolites. Hence, the stringent requirements for prolonged abstinence from caffeine before adenosine MPI - based on limited studies - appear ill-founded.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
22
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 32 publications
5
22
0
1
Order By: Relevance
“…60 A number of studies have investigated the effects of caffeine consumption on the MPI results using adenosine stress finding some effect on imaging, 61 but often no significant effect. 62,63 The data on regadenoson are somewhat mixed with an animal study reporting that caffeine did not affect the maximum increase in Table 5. n/a coronary blood flow, but that the duration of hyperemia was shorter.…”
Section: Caffeine and Coronary Vasodilatorsmentioning
confidence: 92%
“…60 A number of studies have investigated the effects of caffeine consumption on the MPI results using adenosine stress finding some effect on imaging, 61 but often no significant effect. 62,63 The data on regadenoson are somewhat mixed with an animal study reporting that caffeine did not affect the maximum increase in Table 5. n/a coronary blood flow, but that the duration of hyperemia was shorter.…”
Section: Caffeine and Coronary Vasodilatorsmentioning
confidence: 92%
“…В работе Lee J et al про-водилась оценка виляния приема кофеина на площадь стресс-индуцированного дефекта перфузии миокарда [45]. В работе Venkataraman R.et al показатели размера де-фекта перфузии использовали для оценки вли-яния фармакологического стресс-теста с вазо-дилататором на состояние микроциркуляции миокарда пациентов ИБС после лечения рано-лазином (ингибитор позднего тока ионов натрия в клетки миокарда) [46].…”
Section: Discussionunclassified
“…However, studies investigating the effect of caffeine on adenosine-induced hyperemia reported inconsistent results: We and others have previously reported that caffeine consumption prior to adenosine stress perfusion CMR led to a reduction of ischemic burden on qualitative assessment [4][5][6][7]. Other groups, however, did not observe significant impact of caffeine on stress perfusion defect size [8,9]. Data on (semi-)quantitative assessment of myocardial perfusion are scarce, a submaximal hyperemic effect of adenosine after caffeine consumption is supposed [10], and seems reasonable.…”
Section: Introductionmentioning
confidence: 87%